Examining the influence of group diversity on the functioning of community‐based participatory research partnerships: A mixed methods study. Issue 1 (7th November 2022) - Chandanabhumma, P. Paul; Fàbregues, Sergi; Oetzel, John; Duran, Bonnie; Ford, Chandra
Abstract: Public health has endorsed the use of community‐based participatory research (CBPR) to address health inequities involving diverse and marginalized communities. However, few studies have examined how group diversity among members of CBPR partnerships influenced how well the partnerships achieve their goals of addressing health inequities through equitable collaboration. We conducted secondary, convergent, mixed methods analysis to (1) evaluate the association between group diversity and participatory decision‐making within CBPR partnerships, and (2) identify the perceived characteristics, benefits, and challenges of group diversity within CBPR partnerships. Using data from a cross‐site study of federally funded CBPR partnerships, we analyzed and integrated data from surveys of 163 partnerships ( n  = 448 partners) and seven in‐depth case study interviews ( n  = 55 partners). Quantitatively, none of the measured characteristics of group diversity was associated with participatory decision‐making within the partnerships. Qualitatively, we found that partnerships mainly benefited from membership differences in functional characteristics (e.g., skillset) but faced challenges from membership differences in sociocultural characteristics (e.g., gender and race). The integrated findings suggest the need to further understand how emergent group characteristics and how practices that engage in group diversity contribute to collective functioning of the partnerships. Attention to this area can help promote health equity achievements of CBPR partnerships. Highlights: Understanding how group diversity shapes the collaborative functioning of a community‐based participatory research (CBPR) partnership to address health inequities is important. We examined how group diversity influenced the collective functioning of CBPR partnerships using a mixed methods approach. Quantitatively, we found that differences among members in demographic backgrounds did not influence participatory decision‐making. Qualitatively, we found that partnerships benefited from differences among members in functional backgrounds but faced challenges from differences in social and cultural backgrounds. Fostering equitable practices that support the range of group diversity can enhance the success of CBPR.